Collaborative approaches to stroke recovery: overcoming challenges and implementing strategies - Shuranova, Lesia; Vacková, Jitka; Rimárová, Kvetoslava; Hryshchuk, Andriy (Psychosomatic Medicine and General Practice, 2024)
Rationale and purpose: Our study focuses on the importance of timely and effective rehabilitation in the context of the global problem of ischemic stroke and its consequences for health and society. With stroke as a leading cause of disability and mortality worldwide, this study seeks to identify how rehabilitation processes can be improved through coordinated care that encompasses various aspects of treatment and support for patients and their families. This work seeks to identify potential improvements in stroke care that can improve patient quality of life. The impact of stroke extends beyond the immediate health implications to long-term disability, affecting not only the patients but also their families and communities. As such, the urgency for improving rehabilitation processes cannot be overstated. Stroke rehabilitation is a complex and multifaceted process that requires a comprehensive approach to effectively restore function and improve the quality of life for survivors. Our research seeks to delve into the intricacies of stroke rehabilitation, exploring how it can be enhanced through coordinated care that integrates various aspects of treatment and support. The aim is to develop a more effective rehabilitation framework that addresses the diverse needs of stroke patients, facilitating their recovery and reintegration into society. Key to this investigation is the identification of potential improvements in the rehabilitation process. We aim to highlight the significance of a coordinated and integrated approach, which includes medical treatment, physiotherapy, psychological support, and social care. By examining current practices and pinpointing areas for enhancement, we seek to propose strategies that can lead to better patient outcomes and a higher quality of life post-stroke. One of the primary objectives of our study is to emphasize the importance of initiating rehabilitation promptly after a stroke. Delays in rehabilitation can significantly hinder recovery, leading to prolonged disability and a decrease in the potential for regaining lost functions. Our research will investigate the optimal timing for rehabilitation interventions and how timely care can be ensured within various healthcare settings. Stroke rehabilitation should not be confined to physical recovery alone. It must encompass a holistic approach that addresses the psychological, cognitive, and social needs of patients. We will explore how multidisciplinary teams, including neurologists, physiotherapists, occupational therapists, psychologists, and social workers, can work together to provide comprehensive care that meets all aspects of a patient’s recovery needs. The role of family and community support is pivotal in the rehabilitation process. Our study will examine how involving patients’ families and community resources can enhance the effectiveness of rehabilitation. We will assess the impact of family education, community-based rehabilitation programs, and support networks on patient outcomes. With advancements in medical technology and therapeutic methods, there is a growing potential to improve rehabilitation outcomes through innovative techniques. Our research will explore the latest advancements in stroke rehabilitation, including the use of robotics, virtual reality, tele-rehabilitation, and other cutting-edge technologies. We aim to evaluate their effectiveness and feasibility in different healthcare settings. Ensuring that patients have access to quality rehabilitation services is a significant challenge, particularly in low-resource settings. Our study will address issues of accessibility, including the availability of rehabilitation facilities, trained professionals, and financial barriers. Additionally, we will explore strategies to raise awareness about the importance of rehabilitation among patients, families, and healthcare providers. Based on our findings, we aim to provide evidence-based recommendations for policy and practice. These recommendations will be geared towards improving the coordination and delivery of rehabilitation services, ensuring that patients receive timely, comprehensive, and continuous care. We will advocate for policy changes that support the integration of rehabilitation into the broader healthcare system, promoting long-term sustainability and effectiveness. In conclusion, our study is dedicated to advancing the field of stroke rehabilitation by identifying and addressing key areas for improvement. Through a coordinated and integrated approach, we seek to enhance the recovery process, ultimately improving the quality of life for stroke survivors and reducing the burden of disability on society. Background: a number of collaborative approaches to stroke recovery are based on an understanding of the complexity of the process and the need for an integrated approach to treatment and rehabilitation. Key aspects include: Individualization of the approach: each patient has unique needs and characteristics that require personalized treatment and rehabilitation programs. Multimodal approach: the use of various treatment methods (drug, physiotherapeutic, psychological, etc.) to achieve optimal results in the restoration of functions. Comprehensive needs assessment: consideration of physical, mental, social and cognitive aspects of recovery to develop an individualized strategy. Integration of different specialists: involvement of a team of medical, rehabilitation and social workers for a comprehensive approach to the patient. Education and support of the patient and family: providing information, teaching self-care skills and supporting the psychological state of the patient and his relatives. Material and Methods: Using a qualitative approach, we conducted semi-structured interviews with professionals involved in stroke care in two hospitals. Participants included rehabilitation therapists, social workers, psychologists, occupational therapists, physiotherapists, nurses, and general practitioners involved in the rehabilitation process. A total of 131 professionals were interviewed and asked for their impressions and experiences on the effectiveness of rehabilitation strategies and cooperation between different medical team members. The data was analyzed using ATLAS.ti software, which allowed us to identify key themes and patterns in the responses. Results: Coordinated rehabilitation using an interprofessional approach is critical for maximizing function recovery after stroke. Effective communication and interaction between team members, psychological support, and active family involvement in rehabilitation were emphasized. However, challenges were identified, including limited access to rehabilitation services and insufficient awareness of available resources and rehabilitation programs among patients and their families. Conclusions: Effective coordinated rehabilitation, including interprofessional collaboration, is key to the successful recovery of patients after ischemic stroke. An important aspect is the involvement and support of the patient's family and increasing accessibility and awareness of rehabilitation services. To ensure more effective and patient-centered care, integrated care models should be developed to improve the exchange of information between patients, their families, and medical professionals and strengthen the role of the family in the rehabilitation process.